Luiz Francisco Rebello e a censura: diálogos com a História - Serôdio, Maria Helena (2018)
Denouncing and exposing censorship procedures has been one of Luiz Francisco Rebello’s (1924-2011) most visible lines of action, whether in his public interventions, his theatrical practice, his playwrighting or in his theatre historiography. In this essay, we remember and discuss some key moments of Rebello’s resistance to censorship: his intervention as keynote speaker in the International Federation for Theatre Research Lisbon, (2009); his controversial direction of the Companhia do Teatro Municipal, performing in the municipal venue Teatro São Luiz (1971); his participation in the organization of a conference cycle on German documentary-theatre (1972); and in the 2nd Republican Congress, where he discussed the situation of theatre in Portugal (Aveiro, 1969). We also look back on his play, Portugal, anos 40, directed by Carlos Avilez (at the Calouste Gulbenkian Foundation, 1982).